EVALUASI KEBERLANJUTAN PROGRAM PENGEMBANGAN KAPASITAS SDM PENGENDALIAN KARHUTLA DENGAN METODE RAPFIRE - Mochamad Asep Maksum; M. Syamsul Maarif; Lailan Syaufina; Diah Zuhriana (Diponegoro University, 2019)
Forest and land fires in Indonesia are mostly caused by human factors, therefore human resources are an important element that needs to be considered in the prevention and control of forest and land fires. One of the important efforts in anticipating the ongoing recurrence of forest and land fires in Indonesia is by preparing human resources who have the capacity to control the forest and land fires in the field. Several human resource capacity building programs to control forest and land fires have been developed in Indonesia, but are considered not to have played a significant role in controlling forest and land fires in Indonesia. This study aims to evaluate the sustainability of the human resources capacity development program that has been running so far, by building and implementing the Rapfire method through a multidimensional scaling approach. The results of the study show that the forestry human resource capacity development program with community participation tends to have a low level of sustainability, therefore it needs to receive development priorities. The study also found that the main leverage factors that influence the level of sustainability are in the input dimension, including the recruitment system, program management institutions, and budgeting systems. Leverage factors are important attributes that need to be considered and get policy priorities in order to maintain or improve the sustainability status of the human resources capacity development program for forest and land fires control in Indonesia